2016
DOI: 10.5194/jsss-5-301-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mobile and static assessment of biomass in heterogeneous grassland with a multi-sensor system

Abstract: Abstract. The present study aimed to test a mobile device equipped with ultrasonic and spectral sensors for the assessment of biomass from diverse pastures and to compare its prediction accuracy to that from static measurements. Prediction of biomass by mobile application of sensors explained > 63 % of the variation in manually determined reference plots representing the biomass range of each paddock. Accuracy of biomass prediction improved with increasing grazing intensity. A slight overestimation of the true… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
2
9
0
4
Order By: Relevance
“…These results paralleled with the results from previous studies that come from the same geographical region [15,18]. The study from Safari et al [32] obtained linear regression models with NDSI with R 2 of 0.58 and 0.49 for CP and ADF, respectively. Moreover, the results from Biewer et al [15] reported R 2 values of 0.33 and 0.13 R 2 for CP and ADF models with SR, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results paralleled with the results from previous studies that come from the same geographical region [15,18]. The study from Safari et al [32] obtained linear regression models with NDSI with R 2 of 0.58 and 0.49 for CP and ADF, respectively. Moreover, the results from Biewer et al [15] reported R 2 values of 0.33 and 0.13 R 2 for CP and ADF models with SR, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The most frequently applied statistical modelling method is the linear regression (simple linear, step-wise linear) with selected highly correlated spectral features, such as wavebands [20,27], normalised difference spectral indices (NDSIs) [18,24,28], spectral ratios (SRs) [15,29], and other well-known vegetation indices (e.g., NDVI, SAVI, NDRE) [17,23]. Predictive modelling (also known as machine learning) algorithms, such as partial least squares regression (PLSR) [16,27,[30][31][32], random forest regression (RFR) [24,33,34], and artificial neural network [20,21,35], were employed to estimate forage quality parameters using highly correlated spectral reflectance data. Predictive modelling algorithms frequently enhanced the predictive capability compared with the simpler linear regression models [24,34].…”
mentioning
confidence: 99%
“…Furthermore, the results indicate that for a successful estimation of biomass, height information alone is not enough. Evolving sensor fusion approaches might improve the model prediction performance, as it has been shown for example for grassland biomass [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative devices to plate meter readings, using ultrasonic scanning, that can be towed behind an all-terrain vehicle have been developed (Fricke & Wachendorf, 2013), but accuracy is lower in a moving sensor than for static assessments (Safari, Fricke, Reddersen, Mockel, & Wachendorf, 2016). In future, measurements of herbage mass could be automated using robotically controlled mini-tractors (Yule, 2017) or by using electromagnetic reflectance at different wavelengths to develop vegetative indices to predict forage characteristics (Perez-Sanz, Navarro, & Egea-Cortines, 2017).…”
Section: Grazing Managementmentioning
confidence: 99%
“…In future, measurements of herbage mass could be automated using robotically controlled mini-tractors (Yule, 2017) or by using electromagnetic reflectance at different wavelengths to develop vegetative indices to predict forage characteristics (Perez-Sanz, Navarro, & Egea-Cortines, 2017). However, more improvement would be required in these technological devices since results of an ultrasonic distance sensor assessed by Fricke, Richter, and Wachendorf (2011) were promising but could not exceed prediction accuracies ranging between R 2 = .80 and .82 in legume-grass mixtures (Fricke et al, 2011), and the accuracy decreases (from R 2 = .73 to .52) as the herbage mass increases (Safari et al, 2016).…”
Section: Grazing Managementmentioning
confidence: 99%